2018
DOI: 10.1115/1.4040852
|View full text |Cite
|
Sign up to set email alerts
|

Aerothermodynamics and Exergy Analysis in Radial Turbine With Heat Transfer

Abstract: This study was motivated by the difficulties to assess the aerothermodynamic effects of heat transfer on the performance of turbocharger turbine by only looking at the global performance parameters, and by the lack of efforts to quantify the physical mechanisms associated with heat transfer. In this study, we aimed to investigate the sensitivity of performance to heat loss, to quantify the aerothermodynamic mechanisms associated with heat transfer and to study the available energy utilization by a turbocharger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Based on the flow thermal energy conversion ratios, the design of a heat exchanger was improved for better waste heat recovery [3]. In particular, many turbocharger studies focused on the utilization of energy carried by ICE pulsating flows, such as the impacts of different unsteady inlet conditions [4][5][6] along with reducing the thermal dissipation of exhaust pulses upstream of the turbine [7][8][9] and optimizing the configurations of turbocharging systems [10,11], to name a few.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the flow thermal energy conversion ratios, the design of a heat exchanger was improved for better waste heat recovery [3]. In particular, many turbocharger studies focused on the utilization of energy carried by ICE pulsating flows, such as the impacts of different unsteady inlet conditions [4][5][6] along with reducing the thermal dissipation of exhaust pulses upstream of the turbine [7][8][9] and optimizing the configurations of turbocharging systems [10,11], to name a few.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, the energy quantities inside the ICE system can be discussed in specific (i.e., the unit mass basis) and mass flow rate based forms. The specific energy quantity as an intensive property is commonly used to compare the energy transport by unit mass under different operating conditions [7,14]. For instance, the specific exhaust gas enthalpy and exergy in a gasoline compression ignition engine were compared to indicate the input energy change of the turbocharger and waste heat recovery efficiency under different combustion strategies [14].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Usually, a time step corresponding to a degree of rotation of 1 deg is recommended. Some cases might however allow for a larger time step size (e.g., Lim et al (2018) [16]). Depending on the application, the benefit of rotating the blades using the RBM approach and therefore obtaining a physically accurate solution can outweigh the high computational effort.…”
Section: Fan Modellingmentioning
confidence: 99%
“…In an experimental campaign, Shaaban and Seume [8] registered a 55% turbine power decrease compared to adiabatic conditions, demonstrating the effectiveness of thermal insulation to increase the turbine power. On the numerical side, Lim et al [9] reported a decrease of the turbine power up to 10%, for increasing levels of heat transfer, compared to adiabatic conditions.…”
Section: Introductionmentioning
confidence: 99%